Scar Revision: Surgical and Nonsurgical Options - Kadakia, Sameep; Ducic, Yadranko; Jategaonkar, Ameya; Chan, David (Facial Plastic Surgery, 2017)
Facial scarring represents a challenging issue for the facial plastic surgeon owing to the unpredictable and variable nature of scar formation. The psychologic, cosmetic, and functional implications of facial scars oftentimes necessitate revision. It is important for the facial plastic surgeon to be aware of the invasive and noninvasive options to best educate patients in terms of treatment modalities. As there are multiple options available with no single option touted as superior, management of expectations and patient motivation will allow for realistic treatment planning with the greatest change of success.
Keywords: scar revision; topical; surgical